Clinical and Radiographic Comparison of Splinting Constructs for Distal Radius Fractures: An Effort to Free the Elbow. Issue 9 (September 2022) - Stevens, Nicole M.; Pean, Christian; Norris, Zoe; Tejwani, Nirmal
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To compare short-term functional outcomes, reduction loss, and rates of surgery for distal radius fractures initially immobilized with a traditional sugar-tong splint versus clamshell splint freeing the elbow. Design: Prospective randomized trial. Setting: Level 1 trauma center. Patients: Eighty-nine consecutive patients sustaining distal radius fractures were enrolled between 2018 and 2020. Short-term first follow-up (1–2 weeks) radiographic parameters and 6 weeks for functional questionnaires were established to assess initial outcomes. Main Outcome Measures: The main outcome measures were reduction loss based on radiographic criteria, rate of surgery, and short-term patient functional outcome using the Disabilities of the Arm, Shoulder, and Hand (DASH) score. Results: There were no differences noted in DASH scores ( P -value = 0.8) or loss of reduction ( P -value = 0.69), and splint type was not correlated with likelihood to have surgery ( P = 0.22). A binomial regression model demonstrated splint type was not a significant predictor variable of loss of fracture reduction in the regression model. Conclusions: These results suggest both sugar-tong splint and clamshell splint construct are acceptable options in the acute management of distal radius fractures. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.